PENGARUH TINGKAT SUKU BUNGA DEPOSITO, NILAI TUKAR, DAN JUMLAH UANG BEREDAR TERHADAP LAJU INFLASI (IHK) DI INDONESIA - SARI B01108016, SUHARNI PRATAMA (Jurnal Pembangunan dan Pemerataan, 2014)
This thesis of title is â€œThe influence of the deposit interest rate, exchange rate and the amount outstanding on the rate of inflation (IHK) in Indonesiaâ€. The purpose of this study is to analyze the effect of the deposit interest rate and money supply on inflation rate in Indonesia. Â  This study uses qualitative methods, namely by processing secondary data then analyzed the research object in accordance with the purpose of research. The data used are secondary data sourced from the period 2008-2012 and also source by www.bi.go.id. Â  From these results it can be concluded that the interest rate gives a negative and significant effect on inflation in Indonesia, with effect of -2,22%. While the exchange rate gives a positive and significant effect on inflation Indonesia with effect of 3,12%. In addition to interest rates, variable Money Supply (JUB) also gives a negative effect and influence exerted significant inflation in Indonesia, with the effect of -2.06%. Â  Â  Keywords: Deposit Interest Rate, Exchange Rate, the amount outstanding on the rate, Inflation (IHK)